DESAIN SIMULASI PERFORMANSI KODE ORTHOGONAL GOLD PADA KANAL MULTIPATH FADING - Khairunnisa Yasmine, Arzalia; Pramaita, Nyoman; Wirastuti, N.M.A.E.D (Jurnal SPEKTRUM, 2022)
Improved wireless communication system generate the various advanced technologies, one of which is spread spectrum technique. This technique working by multiplying dots bits information which have a large period with spreading code that have a smaller periode, which makes bit periode will follow the code periode. In order to maximize performance of this technique, an efficient code is required to reduce the occurrence of interference. The purpose of this study was to see how the variation of multipath components affected the work of the orthogonal gold code. This study compares BER vs. Eb/No for multipath components 10, 15, and 20 using code length 32, 8 users, and BPSK modulation. The multipath component 10 exhibits the best BER value, which is impacted by the degree of interference indicated by the size of the ACF value. and CCF on a non-zero shift.